Analysis of the Advantages and Disadvantages of Using Autodesk Revit for the Dean Building of the Faculty of Education, Universitas Negeri Semarang - Yuvita, Rizky Lucky; Budiwirawan, Agung (Universitas Negeri Semarang, 2022)
Abstract. Building Information Modeling (BIM) as a supporting software of the fourth phase of the industrial revolution in Indonesia in the construction sector is a digital technology mode to increase the efficiency and accuracy of construction work to avoid mistakes during the planning to the implementation period. This study uses the Autodesk Revit application to provide the output of working drawings, 3D modeling, and calculate the volume and cost of work carried out in the Dean building of the Faculty of Education, Universitas Negeri Semarang. The purpose of this study is to determine the advantages and disadvantages of using Autodesk Revit for planning the Dean building of the Faculty of Education, Universitas Negeri Semarang. The results of this study are the advantages of using Autodesk Revit for building modeling, including providing convenience with design integration in one application, and avoiding crashes between designs. Autodesk Revit also has weaknesses, such as the need for high hardware specifications on the device, high license prices, the application it is necessary to create a new material family according to the design and size required, Autodesk Revit cannot calculate the preparatory work because the calculation of the volume and cost of Autodesk Revit work is limited to data input.